IoT Bicycle Speedometer and Tail Light With Anti-theft Alarm GPS and SMS notification Security System: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
As time changes, the Internet of Things (IoT) describes a network of physical objects thatmanages all the essential human needs in urban areas. The researchers decided to innovatean IoT Controller for a Smart Bicycle, which is an IoT Bicycle Speedometer and Tail Light withAnti-Theft Alarm GPS and SMS Notification Security System, which is IoT-based with sensorsand modules. The main goal of this research is to aid them in being safe, preventing stolenbicycles, and tracking their speed in real time by using their smartphone.The results after testing: when the cyclist opens the device, the cyclist will hear a beep code;the first Beep is for Wi-Fi Connected, the Second beep for Blynk Connected, the Double beepfor SMS Notification, and the last is a triple beep for IR proximity sensor and all componentsare ready to function and manually controlled via Blynk application. Also, when the prototypeis triggered, the GSM module will send a message to the user containing the GPS location. Insound alarm results, 1m is around 95dB, and 5 meters is 82 dB. The battery capacity is3000mA, with a 2-hour and 31-minute life duration at 3.7V. The rechargeable battery is themain power source. The evaluation of the survey shows that respondents agree with theproposed prototype.The technologies used were compatible with the microcontroller, such as ESP32s, andshowed success in the operation of the prototype. It contains a GPS module to track thelocation of the bicycle using a smartphone and also an anti-theft alarm for security features toensure the bicycle is safe. Therefore, it is concluded that the ESP32s microcontroller is aneffective electronic gadget to fabricate a prototype IOT Bicycle Speedometer and Tail LightSignal with an anti-theft alarm GPS and SMS Notification Security System.
Keywords: Computer Science; Engineering